Alumina effect on the structure and properties of calcium aluminosilicate in the percalcic region: A molecular dynamics investigation - Atila, Achraf; Ghardi, El Mehdi; Hasnaoui, Abdellatif; Ouaskit, Said (Journal of Non-Crystalline Solids, 2019)
We rely on molecular dynamics simulations to investigate and discuss the effect of alumina content on the thermodynamic, elastic and structural properties of calcium aluminosilicate glasses in the light of available experimental data. The alumina content varies from low to intermediate ranges by considering compositions of (CaO [sbnd] SiO2)(1−x)(Al2O3)x where x = 0–30 mol%. The glass transition temperature was found by referring to the concept of inherent structure energy while elastic properties were computed using two methods: the first is via molecular statics using energy minimization and the second one by performing molecular dynamics at a finite temperature. We suggest a correlation between structural changes, mechanical properties and glass transition temperature, through an analysis of the short and medium range orders. The results show that by increasing Al2O3 content, an increase in the population of bridging oxygens and oxygen tricluster is observed while free oxygens tend to vanish. Regions with rich Al [sbnd] O [sbnd] Al linkages start to appear as shown by the aluminium avoidance parameter, which is also accompanied with an increase of the glass transition temperature and elastic moduli.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Aluminium avoidance parameter; Calcium aluminosilicate; Elastic properties; Glass transition; Molecular dynamics